ARE BUS DRIVERS EFFECTED BY STRESS RELATED BRUXISM: A “See It Through” ANALYSIS USING CROSS SECTIONAL STUDY DESIGN - Subashini V1, Prabu D2, Bharathwaj V.V3, Sindhu R3, Dinesh Dhamodhar4, Sathiyapriya S3, Rajmohan M4, Vishali M5 (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2023)
BACKGROUND: Bruxism, also known as Bruxomania, is the grinding of teeth at night and during the day. The aetiology for bruxism may be local, systemic, psychological or occupational. The psychological reasons are anxiety, emotional stress etc., The current generation worldwide is commonly affected by a factor called ’stress’. Stress also has its effect on the human body by various means. AIM: The study has been done to evaluate the commonness of bruxism among the bus drivers in Chennai City in relation to stress. MATERIALS AND METHOD: A cross-sectional study was made among the bus drivers of Chennai city using simple random sampling. The participants (N=101) were interviewed. A modified version American academy of stress questionnaire was used, which consisted of questions related to stress, work experience, working hours, bruxism etc., The categories were recorded on a ten-unit scale, and further statistical analysis was done with SPSS software using Chi-square and regression analysis. P value < 0.05 is considered significant. RESULTS: Most of the mass reported the presence of diurnal bruxism. Diurnal bruxism was co-related with factors like work experience, no satisfaction in the job and relatively stress ( P value less than 0.05 gets significant). Years of work increase with stress accentuation, indicating the prevalence of diurnal bruxism. Hence, this analysis shows that work and stress have a significant role in bruxism among bus drivers. CONCLUSION: The study reveals that the work pressure, along with the increase in the duration of work, stress-related factors etc., may cause bruxism. Hence the conclusion was made that stress affected the oral cavity, causing bruxism among the bus drivers of Chennai city. KEYWORDS: Stress, Bruxism, Bus drivers, Work pressure